Family support and self-management behavior among clients with hypertension: A Cross-Sectional Study - Rasdiyanah Rasdiyanah; Nurul Farah Dila; Nur Al Marwah Asrul; Eny Sutria; Nur Andani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Hypertension remains a leading global public health challenge. The World Health Organization (WHO) reported that the number of adults living with hypertension increased from 650 million in 1990 to 1.3 billion in 2019, contributing substantially to premature mortality and disability worldwide. In Indonesia, hypertension is a major non-communicable disease and a significant contributor to cardiovascular morbidity. Effective blood pressure control requires sustained self-management, including adherence to medication, dietary modifications, physical activity, and stress management. Family support is theoretically considered a reinforcing factor for improving self-management behavior among patients with chronic diseases. To examine the relationship between family support and self-management behavior among clients with hypertension at the Rappokalling Community Health Center, Makassar City. Research Methodology: A quantitative cross-sectional study was conducted among 164 hypertensive clients selected using purposive sampling. Self-management was measured using the High Blood Pressure Self-Care Profile (HPB-SCP), and family support was assessed using a validated Family Support Questionnaire. Data were analyzed using descriptive statistics and Spearman’s rank correlation test with a 95% confidence interval (α=0.05). Results: Most respondents reported adequate family support (66.5%) and adequate self-management (95.8%). Spearman’s analysis showed a weak negative correlation between family support and self-management (r = −0.099) with no statistically significant association (p = 0.207; 95% CI). Conclusion: Family support was not significantly associated with self-management behavior among hypertensive clients. Public health interventions should not rely solely on family involvement but also address individual motivational and psychological determinants to improve hypertension self-management.